MODERN DIAGNOSTIC APPROCHES IN CARDIOVASCULAR SYSTEM : AN AN ALYTICAL OVERVIEW (Academicia Globe: Inderscience Research, 2025)
This scientific review explores the most recent and innovative diagnostic methods used in the detection and evaluation of cardiovascular diseases. The article highlights advanced imaging techniques such as cardiac magnetic resonance imaging (MRI) , computer tomography (CT) , angiography and three-dimensional echocardiography , which offer detailed visualization of cardiac structures and blood vessels . It also discusses the role of modern laboratory diagnostics , including high – sensitivity cardiac biomarkers like troponins and natriuretic peptides , which improve the accuracy of early detection . Furthermore, the growing use of wearable devices and telemedicine in continuous cardiovascular monitoring is also addressed. The review aims to provide a detailed analysis of how these modern technologies contribute to faster , more accurate and non-invasive diagnosis , ultimately enhancing patient outcomes and clinical decision-making in cardiovascular care.